Genetic and epigenetic changes of NKIRAS1 gene in human renal cell carcinomas - Gerashchenko, G.V.; Bogatyrova, O.O.; Rudenko, E.E.; Kondratov, A.G.; Gordiyuk, V.V.; Zgonnyk, Y.M.; Vozianov, O.F.; Pavlova, T.V.; Zabarovsky, E.R.; Rynditch, A.V.; Kashuba, V.I. (Experimental Oncology, 2010)
Renal cell carcinoma (RCC) is the most common malignant tumor of kidney associated with the worst clinical outcome. No molecular markers for RCC diagnostics and prognosis that could be applied in clinics were described yet. Large-scale screening of 3p human chromosome genes/loci in RCC and histologically normal tissues surrounding the tumors using NotI-microarray approach demonstrated that NKIRAS1 gene contained the largest percent of genetic/epigenetic changes in RCC tumor cells. Aim: To validate the results of NotI microarray analysis and study genetic, epigenetic changes, and the expression level of NKIRAS1 gene in human RCC samples. Methods: DNA and RNA were isolated from freshly-frozen renal tumors’ samples (n = 12) and from normal tissues surrounding the tumors. Epigenetic changes (methylation status) of NKIRAS1 were detected by bisulfite sequencing. Genetic changes and expression level were analyzed by Quantitative real-time PCR (qPCR) with SYBR Green. For relative quantification 2-ΔΔCP method was used. Nonparametric tests (Wilcoxon, Kruskal — Wallis and Mann — Whitney) were applied for statistical data analysis using the BioStat software. Results: NKIRAS1 expression was downregulated in 75% of RCC samples (9 of 12) compared with surrounding normal tissue. High grade tumors (3 and 4) showed lower expression of NKIRAS1 at the mRNA level than tumors of low grade (1 and 2). No significant association was found between gene expression level and gender or age. Analysis of NKIRAS1 gene copy number was performed in 19 tumor samples. Changes in the copy number of NKIRAS1 gene were observed in 64% (9 of 14) of cRCC samples. 9 samples displayed ratio ( 0.85) and were considered as normal copy number. Changes in NKIRAS1 gene copy number were detected in all 3 benign oncocytomas, 1 papillary cancer and 1 sarcoma, where hemizygous deletion was observed. No changes in methylation status of NKIRAS1 were found in RCC. Conclusions: We have validated the results of NotI microarray analysis of NKIRAS1 gene in RCC. It was shown the decreased expression level of NKIRAS1 in this type of tumor.